Association of anticholinergic medication and AD biomarkers among cognitively normal late middle‐age adults: Results from the Wisconsin Registry for Alzheimer's Prevention (WRAP). (31st December 2021) - Du, Lianlian; Koscik, Rebecca L; Chin, Nathaniel A; Bratzke, Lisa C; Cody, Karly Alex; Erickson, Claire M; Betthauser, Tobey J; Jonaitis, Erin M; Hermann, Bruce P; Vasiljevic, Eva; Deming, Yuetiva; Mueller, Kimberly D; et al.
Abstract: Background: Studies of anticholinergic (AC) medications (drugs that block acetylcholine neurotransmitter action) have shown associations between the AC medications use, cognitive impairment, and increased dementia risk. Associations between AC medication and AD biomarkers among cognitively normal late middle‐aged adults are unclear. This study examined associations between AC use, cognition, physical health, and amyloid PET measures. Methods: Wisconsin Registry for Alzheimer's Prevention (WRAP) participants with >=3 cognitive composite scores, free of dementia at baseline cognition (n=1262) were included in analyses of cognitive and general health measures; PET amyloid measures were examined in a subset with Pittsburgh Compound B PET imaging (PiB; n=299). Participants were classified as either taking or not taking at least one AC medication at baseline (AC+, n=437; AC‐, n=825; Table 1). Cross‐sectional analysis of baseline associations examined AC+/AC‐ differences in AD‐related cognitive composites (e.g., memory, PACC) and health markers (e.g., depression, comorbidities). Linear mixed‐effects models (LME) examined whether AC modified age‐related cognitive trajectories in APOE ε4 carriers or non‐carriers and PiB positive or negative group. Sensitivity analyses repeated models only in the high AC+ (AC score > 1) group (n=191) relative to the AC‐ group. The statistical threshold for significance was set at P < .05. Results: Mean(sd) age for AC+ and AC‐ participants was 55.4(6.4) and 53.7(6.6). The AC+ group was significantly higher than the AC‐ group on depression scores, BMI, total medications, total comorbidities, and cardiovascular problems (Table 2). The AC groups did not differ on amyloid PET measures (Table 3). At baseline cognition, the AC+ group (n=437) showed lower executive function and PACC3 scores (Figure 1). Longitudinal analyses indicated that AC+ predicted a steeper decline slope in executive function and PACC3 with effects exacerbated in individuals with AD risk factors (Fig. 2‐3, respectively). The slopes of AC + group differed significantly after age 65. Conclusion: AC medication use was associated with faster cognitive decline, particularly among APOE 4 carriers and those with PET‐based evidence of amyloid plaques, suggesting AC use may exacerbate AD‐related cognitive decline in the preclinical time frame. The results have implications for AC usage in older adults with AD risk or biomarker positivity.